Mushroom-Derived Carbon Dots for Toxic Metal Ion Detection and as Antibacterial and Anticancer Agents - Boobalan, T; Sethupathi, M; Sengottuvelan, N; Kumar, Ponnuchamy; Balaji, P; Gulyás, Balázs; Padmanabhan, Parasuraman; Selvan, Subramanian Tamil; Arun, A (ACS applied nano materials, 2020)
Although carbon nanoparticles or quantum dots (C-dots) have been studied extensively for a variety of applications (e.g., photocatalysis, metal ion sensing, antibacterial, cell labeling), a greener synthetic method is highly indispensable. Herein, we report a facile one-step hydrothermal carbonization approach for the synthesis of fluorescent blue/green C-dots using oyster mushroom (Pleurotus species). First, we demonstrate the application of these C-dots as a colorimetric sensor for toxic metal ions detection such as heavy metal Pb2+ ions with the limit of detection (LOD) and limit of quantification (LOQ) of 58.63 μM and 177.69 μM, respectively. Second, we show the application of C-dots as a promising fluorescent probe for DNA recognition through the electrostatic intercalative interaction between ctDNA and C-dots. Third, we demonstrate the efficient antibacterial activity of C-dots against three bacterial strains (Staphylococcus aureus, Klebsiella pneumoniae, and Pseudomonas aeruginosa). Finally, the anticancer activity of C-dots against MDA-MB-231 breast cancer cells is demonstrated.